Taxation and energy: some considerations - de la Vega Rengifo, Beatriz (2021)
Energy is a fundamental element for the development of society and the economic sectors that comprise it. However, it is one of the largest sources of Greenhouse Gas (GHG) emissions, which is why many countries around the globe have seen fit to promote changes in their energy matrix through tax incentives for investment, generation and consumption from less polluting energy sources such as Renewable Energy Resources (RER) and implementation of carbon taxes, among others, to reduce the consumption of fossil fuels.All these actions are part of the global efforts against climate change and the fulfillment of the commitments assumed by all countries that signed the Paris Agreement to reduce GHG emissions at the country level.In this sense, the introduction of carbon taxes in the international contexis analyzed in the following document, offering a contextualization of the changes made in multiple countries, but not without first reviewing some tax incentives on power generation through RER in Peru. Finally, this document includes some comments regarding the need to evaluate a fiscal reform that considers the status of the energy transition and the fight against climate change in Peru. For these purposes, it is added an overview of the international experience with the aim of offering an in-depth analysis of the tax systems evolution about the implementation of taxes related to the energy sector and environmental care.